Assessment of bio-activities of the crude extract and components of Withania somnifera leaves by bioinformatics - Nashi Widodo; Didik Priyandoko; Custer C. Deocaris; Renu Wadhwa; Sunil C. Kaul (Journal of Tropical Life Science, 2010)
Traditional herbal medicines are now increasingly being appreciated with Western models of integrative health sciences and evidence-based approach both in the basic research and clinic scenario. Ashwagandha is a commonly used plant in Ayurvedic, Indian traditional medicine. Medicinal value of Ashwagandha (WithaniasomniferaDunal) extends from anti-inflammatory, anti-arthritic, anti-rheumatic, rejuvenation and anti-cancer. Based on the belief that holistic multi-site mechanism of action offers greater chance of success, the traditional Ayurvedicmedicine practices the use of whole herb or its crude extract. It opposes with the mainstream of pharmaceutical industry that uses single and purified molecules. In the present study, we used bioinformatics approach to reveal the mechanism of action of (i) crude extract of Ashwagandha leaf extract and its purified components, (ii) Withanone and (iii) Withaferin A. Whereas p53-p21 was identified as a common signaling pathway for the three kinds of reagents, specific signaling pathways for Withaferin-A and Withanone were identified. Whereas the crude extract and Withanone were selectively toxic to human cancer cells, Withaferin A showed cytotoxicity to the normal cells too. The study suggested that the crude extract or a combinational formulamay be a superior and safenatural reagent for cancer treatment.